Difficulties of VHF communication in the region of the Valley of the Apurimac, Ene and Mantaro Rivers in Peru: Challenges of a mountainous area and dense vegetation (LACCEI, 2024)
VHF communications in the region of the Valley of the Apurímac, Ene, Mantaro - VRAEM rivers, in Peru, a mountainous region with dense vegetation, are difficult to establish due to the characteristics of the rugged geography, weather conditions and to the vegetation. In this regard, in order to reduce the difficulty of VHF communications in the jungle region, studies have been carried out proposing the use of upper troposphere propagation. However, this technique has several limitations, such as its dependence on specific meteorological conditions and the need for specialized equipment and trained personnel for its use. In addition, in the Amazon region, humidity and clouds can hinder propagation through the upper troposphere, which reduces its effectiveness. Given the strategic importance of the VRAEM region in the fight against drug trafficking and terrorism, the lack of effective communications could jeopardize military operations and the safety of people in the area. In this sense, efforts are being made to improve communications in the region, such as the exploration of alternative technologies and the training of personnel specialized in communications in areas that are difficult to access. The Peruvian Armed Forces in the VRAEM that conduct operations against terrorism and drug trafficking, have carried out various tests and corroborate in practice the technical limitations that scholars raise. Therefore, it is necessary to continue researching and exploring new technological options to improve communications in the region, in order to guarantee the effectiveness and safety of military operations and the protection of the population.